2017
DOI: 10.1155/2017/6439169
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Roles of DNA Double-Strand Breaks

Abstract: Genomic integrity is constantly threatened by sources of DNA damage, internal and external alike. Among the most cytotoxic lesions is the DNA double-strand break (DSB) which arises from the cleavage of both strands of the double helix. Cells boast a considerable set of defences to both prevent and repair these breaks and drugs which derail these processes represent an important category of anticancer therapeutics. And yet, bizarrely, cells deploy this very machinery for the intentional and calculated disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 304 publications
(341 reference statements)
1
15
1
1
Order By: Relevance
“…Double-strand breaks (DSBs) are known to be one of the most lethal types of DNA lesions in mammalian cells 1 , 2 . Exogenous and endogenous DNA damaging agents such as radiation, carcinogens, and replication stress destroy the integrity and stability of genome, and contribute to the pathogenesis of various diseases, including developmental defects, immune deficiency, premature aging, and cancer 1 , 3 5 . To eliminate the risk of DSBs, cells have evolved a complex network to sense and repair damaged DNA, collectively known as the DNA damage response (DDR) pathway 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Double-strand breaks (DSBs) are known to be one of the most lethal types of DNA lesions in mammalian cells 1 , 2 . Exogenous and endogenous DNA damaging agents such as radiation, carcinogens, and replication stress destroy the integrity and stability of genome, and contribute to the pathogenesis of various diseases, including developmental defects, immune deficiency, premature aging, and cancer 1 , 3 5 . To eliminate the risk of DSBs, cells have evolved a complex network to sense and repair damaged DNA, collectively known as the DNA damage response (DDR) pathway 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, researches on the correlation between Rad51 and tumor metastasis are still insufficient. It is well-known that the process of tumor cell invasion and metastasis is also an immune escape process, during which tumor cells in microenvironment escaped the direct attack of immune cells through enhancing DNA damage repair, meanwhile gained the ability against the cytotoxic effects of chemotherapy drugs finally resulting from acquiring some growth advantage [20]. Recently, a study from the Medical Center of Montpellier University in France revealed the key role of DNA repair in the progression of metastatic circulating colon cancer cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…DSBs can be generated "accidentally" by missteps of information processing machineries, i.e., by mistiming of replication, replication-transcription complex conflicts, and replication or transcription through existing DNA damage/secondary structures [13][14][15][16]. DSBs are also purposefully generated as essential intermediates of many nucleic acid metabolism pathways [17][18][19][20] and if such pathways are aborted prematurely, intermediate complexes may be released inappropriately. Unchecked DSBs can be extremely detrimental to cellular health, causing arrests of replication and transcription which may lead to apoptosis.…”
Section: Double-strand Break (Dsb) Repairmentioning
confidence: 99%